Effective Classroom Management: A Sine Qua Non to Effective Teaching in a School Setting - Matthew, Ige Akindele (International Journal of Educational Studies, 2022)
A classroom is a place where a teacher teaches the learners and where the learners learn from a teacher. Being the workshop of a teacher where teaching and learning take place, the management of a classroom needs to be accorded priority attention. It is believed that if classroom management is given attention, so will effective teaching be achieved. In this paper, the issue of effective classroom management is examined, with a focus on the elements, such as the effective use of chalkboard, communication, use of teaching aids/instructional materials, evaluation of lesson, and management of behavioural challenges, such as noise-making, sleeping, fighting, reading, writing, eating, hissing, foot-dragging, just to mention a few; as well as the management of classroom environment, are examined. The paper recommends how to achieve effective classroom management and ultimately, effective teaching in a classroom setting, such as effective use of chalkboard, communication, use of instructional materials, evaluation of lesson, and management of behavioural challenges.